Teacher and Students of Music Interaction in English Classroom Through Face-To-Face Learning System at SMKN 11 Medan - Kaswari, Gisti Dila; Nuran, Ade Aini (Universitas Negeri Medan, 2023)
This research dealt with classroom interaction between teacher and students of music in English classroom. This research was conducted to determine the most dominant of interaction in the classroom and the occurrences of classroom interaction between teacher and students of music in English classroom through face-to-face learning system at SMKN 11 Medan. This research used qualitative research. The data were verbal interaction in the form of spoken texts of teacher and students of music during teaching and learning English and were then analyzed by applying the Flanders interaction analysis categories system (FIACS) as interaction model proposed by Flanders (1970). They were collected through observation and audio recording for two class meetings. The results showed that the verbal interaction was most dominantly by teacher talk (64%). In the part of teacher talk, the ratio of indirect teacher talk had the highest percentage (39%) than the ratio of direct teacher talk (29%). Particularly on the category 4 asking question of indirect teacher talk. It was indicated that teacher intentionally asked questions related to the topic material to the students. Meanwhile, the result of the interactions in English classroom was mostly happened by content cross (35%) which consists of category 4 asking questions and 5 lecturing. It showed that teacher mostly provided the students with the questions on the sidelines of lectures during learning process.